PENGEMBANGAN WEBSITE COMPANY PROFILE PADA PONDOK PESANTREN MODERN (PPM) DAAR EL-KHAIRAT - Adha, Rizki; Anwar, Syaiful (Universitas Siber Indonesia, 2024)
The Covid-19 virus entered Indonesia at the end of 2019, changing people's lifestyles, including in the education sector. Large-scale social restrictions require school activities to be carried out online. The impact of the pandemic has caused schools to have difficulty marketing or introducing schools to the general public. Using a website-based company profile can be a new way to market or promote schools in attracting new prospective students. Prospective new students can access information and also register online on the website. Daar El-Khairat Modern Islamic Boarding School is one of the Islamic boarding schools that is transitioning to using websites to promote Islamic boarding schools and register new students online. The aim of this research is to develop a website-based company profile that can be used by the Daar El-Khairat Modern Islamic Boarding School (PPM) as a promotional medium, introducing Islamic boarding schools, and registering new students. The method used in the process of developing a website-based company profile is using the waterfall method. The results of testing using the black box method show that the menus on the website meet expectations and can operate smoothly without any bugs or errors.